2016
DOI: 10.1002/pen.24357
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, thermal, rheological, and mechanical properties of PP/EVOH blends compatibilized with PP‐g‐IA

Abstract: We prepared some blends of polypropylene (PP) and ethylene vinyl alcohol (EVOH) with and without a compatibilizer. As a new compatibilizer, we synthesized polypropylene grafted with itaconic acid (PP‐g‐IA) using Brabender mixing system. We investigated the morphological, thermal, rheological, and mechanical properties of a compatibilized blends (PP/EVOH/PP‐g‐IA) and not compatibilized blends (PP/EVOH). Our experiments showed that carboxylic acid groups in PP‐g‐IA and hydroxyl group in EVOH formed strong in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…Thus, the appearance of both peaks for the polymers blended indicate that there are two phases that are immiscible but compatible. The results indicate that the addition of EVA on a PP matrix decreased the initial crystallinity of the PP phase from 34% to approximately 16% due to the introduction of a high amorphous polymer lowering the chemical potential of crystallization of both polymers [ 42 ], while for the PP/EVOH blends, the crystallinity is not significantly affected. DSC showed that the crystalline phases of the polymers are distinct and each polymer has an independent crystallization process [ 40 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the appearance of both peaks for the polymers blended indicate that there are two phases that are immiscible but compatible. The results indicate that the addition of EVA on a PP matrix decreased the initial crystallinity of the PP phase from 34% to approximately 16% due to the introduction of a high amorphous polymer lowering the chemical potential of crystallization of both polymers [ 42 ], while for the PP/EVOH blends, the crystallinity is not significantly affected. DSC showed that the crystalline phases of the polymers are distinct and each polymer has an independent crystallization process [ 40 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is well known in the literature that both blends are immiscible but compatible, forming a spherical dispersed phase in the polyolefin matrix (using the concentrations of PP and ethylene- and polar-monomer-based copolymer proposed in this research). This always occurred unless a compatibilizer is added where a co-continuous phase can be formed [ 35 , 42 , 46 , 47 ]. Comparing Figure 1 a,c, the micrographs clearly show three different morphologies: a co-continuous phase for the PP/EVA systems (regardless the content of VA), a spherical- shaped dispersed phase for PP/EVOH44 ( Figure 1 g) and a fibrillar shape dispersed phase for PP/EVOH38 ( Figure 1 e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important universal plastic, polypropylene (PP) has numerous applications in real life, such as containers, automobiles, nonwoven fabrics, construction, coverings, wires and cables, electronic and electric industry due to its versatility, high performance‐to‐cost ratio, easy processing, and excellent mechanical property . Unfortunately, when exposed to fire or heat source, the flammability and melt dripping problems of PP materials severely restrain its further application in more fields.…”
Section: Introductionmentioning
confidence: 99%
“…Lertwimolnun and Vergnes fabricated the PP/organoclay nanocomposites, in which system the PP grafted with maleic anhydride (PP‐ g ‐MA) was used to promote the clay distribution. Kim et al blended PP and ethylene vinyl alcohol (EVOH) with and without 10 wt% compatibilizer polypropylene grafted with itaconic acid (PP‐ g ‐IA), SEM pictures showed that PP and EVOH blended more uniformly with PP‐ g ‐IA than PP/EVOH blends without PP‐ g ‐IA, and there was no obvious “sea‐island” structure in the PP/EVOH/PP‐ g ‐IA blends. Bettini et al prepared PP/coir fiber (CF) composites, and incorporated PP‐ g ‐MA as compatibilizer, SEM micrographs indicated that PP and CF contacted closer with PP‐ g ‐MA than the blends PP/CF without PP‐ g ‐MA.…”
Section: Introductionmentioning
confidence: 99%